Microsleep disturbances are associated with noradrenergic dysfunction in Parkinson's disease. Issue 8 (20th February 2021) - Doppler, Christopher E J; Smit, Julia A M; Hommelsen, Maximilian; Seger, Aline; Horsager, Jacob; Kinnerup, Martin B; Hansen, Allan K; Fedorova, Tatyana D; Knudsen, Karoline; Otto, Marit; Nahimi, Adjmal; Borghammer, Per; et al.
Abstract: Study Objectives: Parkinson's disease (PD) commonly involves degeneration of sleep-wake regulating brainstem nuclei; likewise, sleep-wake disturbances are highly prevalent in PD patients. As polysomnography macroparameters typically show only minor changes in PD, we investigated sleep microstructure, particularly cyclic alternating pattern (CAP), and its relation to alterations of the noradrenergic system in these patients. Methods: We analyzed 27 PD patients and 13 healthy control (HC) subjects who underwent overnight polysomnography and 11 C-MeNER positron emission tomography for evaluation of noradrenaline transporter density. Sleep macroparameters, as well as CAP metrics, were evaluated according to the consensus statement from 2001. Statistical analysis comprised group comparisons and correlation analysis of CAP metrics with clinical characteristics of PD patients as well as noradrenaline transporter density. Results: PD patients and HC subjects were comparable in demographic characteristics (age, sex, body mass index) and polysomnography macroparameters. CAP rate as well as A index differed significantly between groups, with PD patients having a lower CAP rate (46.7 ± 6.6% versus 38.0 ± 11.6%, p = 0.015) and lower A index (49.0 ± 8.7/hour versus 40.1 ± 15.4/hour, p = 0.042). In PD patients, both CAP metrics correlated significantly with diminished noradrenaline transporter density in arousal prompting brainstem nuclei (locus coeruleus, raphe nuclei) as well as arousal propagating brain structures like thalamus and bitemporal cortex. Conclusions: Sleep microstructure is more severely altered than sleep macrostructure in PD patients and is associated with widespread dysfunction of the noradrenergic arousal system.